Amorphous magnesium phosphate flower-like hierarchical nanostructures: microwave-assisted rapid synthesis using fructose 1, 6-bisphosphate trisodium salt as an organic phosphorus source and application in protein adsorption. Issue 19 (2nd February 2015) - Qi, Chao; Zhu, Ying-Jie; Lu, Bing-Qiang; Wu, Jin; Chen, Feng
Abstract : Amorphous magnesium phosphate flower-like hierarchical nanostructures are synthesized using fructose 1, 6-bisphosphate trisodium salt by the microwave hydrothermal method. Abstract : Magnesium phosphate, as an alternative to well-known calcium phosphate biomaterials and an excellent candidate for biomedical applications, has aroused interest in recent years due to its outstanding biocompatibility and biodegradability. However, to the best of our knowledge, the microwave-assisted hydrothermal rapid synthesis of amorphous magnesium phosphate hierarchical nanostructures using fructose 1, 6-bisphosphate trisodium salt as an organic phosphorus source has not been reported. Herein, we report a simple, one-step and low-cost microwave-assisted hydrothermal rapid synthesis of amorphous magnesium phosphate flower-like hierarchical nanostructures (AMPFHNs) by using fructose 1, 6-bisphosphate trisodium salt (FBP) as an organic phosphorus source. The as-prepared AMPFHNs are formed by self-assembly with amorphous magnesium phosphate nanosheets with a thickness of about 10 nm. The use of FBP as an organic phosphorus source and the microwave hydrothermal time as well as microwave hydrothermal temperature are important factors in the synthesis of AMPFHNs. The AMPFHNs have a high cytocompatibility, and exhibit an excellent ability to promote the adhesion and spreading of the MC-3T3 osteoblasts, and have a relatively high protein adsorption ability using hemoglobin (Hb) as a model protein. The as-prepared AMPFHNs are promising for application in various biomedical fields.